Black bird, blue road - Pasternack, Sofiya (Versify, 2022)
Ever since he was diagnosed with leprosy, Pesah and his fraternal twin Ziva have devoted their lives to finding a cure for his disease. Though Pesah lives separately on the family's property in the Turkic Jewish empire of Khazaria, his uncle doctor recommends that he move to a commune with other leprosy victims. Soon after, Pesah has a dream that the Angel of Death will be coming for him on Rosh Hashanah. Unwilling to accept Pesah's fate, Ziva flees with him to find a cure before the new year. With help from a half-demon boy named Almas who they help along the way, Ziva and Pesah learn of the city of Luz, a place where the Angel of Death cannot go and no one ever dies. The trio embarks on a journey to circumvent their fate by reaching Luz before the Angel reaches them.